Theoretical Prediction of Ultrasonic Velocity in Binary Liquid Mixtures - Shaik. Babu (E-Journal of Chemistry)
Theoretical values of ultrasonic velocity in the binary mixtures of chlorobenzene with benzene have been evaluated at different temperatures from 303.15 K-323.15 K using Nomoto's relation, ideal mixture relation, Junjie's method, collision factor theory and free length theory. Theoretical values were compared with the experimental values and the validity of the theories was checked by applying the chi-square test for goodness of fit and by calculating the average percentage error (APE).